2018
DOI: 10.1148/radiol.2018171539
|View full text |Cite
|
Sign up to set email alerts
|

Association between Screening Mammography Recall Rate and Interval Cancers in the UK Breast Cancer Service Screening Program: A Cohort Study

Abstract: Purpose To determine whether low levels of recall lead to increased interval cancers and the magnitude of this effect. Materials and Methods The authors retrospectively analyzed prospectively collected data from the UK National Health Service Breast Screening Programme during a 36-month period (April 1, 2005 to March 31, 2008), with 3-year follow-up in women aged 50-70 years. Data on recall, cancers detected at screening, and interval cancers were available for each of the 84 breast screening units and for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Double-reading of mammograms is demonstrated to reduce the interval cancer rates compared with single-reading (179). In addition, the expected or accepted recall rate in the program may influence the incidence of interval cancer; by accepting a higher rate of recall, a higher number of subtle findingswhich otherwise may develop and be diagnosed as interval cancer -might be recalled for further assessment compared with a program in which very low recall rates are anticipated (180,181). However, a modelling study demonstrated that an increase in recall rate above approximately 7% resulted in only a slight increase in detection of low grade non-invasive cancers and no further increased detection of invasive and high grade non-invasive cancers (182).…”
Section: Dbt In Screeningmentioning
confidence: 99%
“…Double-reading of mammograms is demonstrated to reduce the interval cancer rates compared with single-reading (179). In addition, the expected or accepted recall rate in the program may influence the incidence of interval cancer; by accepting a higher rate of recall, a higher number of subtle findingswhich otherwise may develop and be diagnosed as interval cancer -might be recalled for further assessment compared with a program in which very low recall rates are anticipated (180,181). However, a modelling study demonstrated that an increase in recall rate above approximately 7% resulted in only a slight increase in detection of low grade non-invasive cancers and no further increased detection of invasive and high grade non-invasive cancers (182).…”
Section: Dbt In Screeningmentioning
confidence: 99%
“…9,16 A study in St James's Hospital, by Healy et al, 25 between 2009 to 2014, documented a 5-year recall rate of 10.9%, suggesting a relatively static recall rate. A recall rate of 23.6%, was documented for MRI surveillance, in Boston, USA, by Lehman et al 26 Although studies do not exist in the area of screening breast MRI, a recent study by Burnside and colleagues 27 demonstrated that lower screening mammography recall rates correlated with higher interval cancer rates. Based on their findings, they suggest that a minimum recall rate may be of value to enable the benefit of preclinical breast cancer diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted in other similar studies, our data are aggregated and anonymized; thus, we do not have access to detailed demographic risk factors beyond age. As a result, we cannot perform subgroup analyses on variables that are known to affect attendance 45 . Finally, we have not considered/excluded women who have developed cancer in the call range after the FPR.…”
Section: Discussionmentioning
confidence: 99%